Implication of different replicons in the spread of the VIM-1-encoding integron, In110, in Enterobacterales from Czech hospitals - Bitar, Ibrahim; Papagiannitsis, Costas C.; Kraftova, Lucie; Marchetti, Vittoria Mattioni; Petinaki, Efthymia; Finianos, Marc; Chudejova, Katerina; Zemlickova, Helena; Hrabak, Jaroslav (Frontiers in Microbiology, 2023)
Background VIM metallo-β-lactamases are enzymes characterized by the ability to hydrolyze all β-lactams. Usually, blaVIM-like genes are carried by class 1 integrons. In the Czech Republic, only sporadic cases of VIM-producing Enterobacterales have been reported in which those isolates carried the VIM-1 carbapenemase-encoding integron In110. However, during 2019–2020, an increased number was reported. Therefore, the aim of the current study was to characterize the genetic elements involved in the increased spread of blaVIM genes. Materials and methods 32 VIM-producing Enterobacterales collected between 2019 and 2020 were subjected to: antimicrobial susceptibility testing, integron analysis, and short reads sequencing. Based on the results, 19 isolates were selected as representative and sequenced using Sequel I platform. Results The 32 VIM-producing isolates exhibited variations in the MICs of carbapenems. Based on short-read data, 26 of the 32 sequenced isolates harbored the blaVIM-1 allele while six isolates carried the blaVIM-4 gene. The most prevalent was the In110 integron (n = 24) and two isolates carried the In4873 class 1 integron. The blaVIM-4 allele was identified in class 1 integrons In1174 (n = 3), In416 (n = 1), In2143 (n = 1) and In2150. Long reads sequencing revealed that the blaVIM was carried by: pKPC-CAV1193-like (n = 6), HI1 (pNDM-CIT; n = 4), HI2 (n = 3), FIB (pECLA; n = 2) and N (n = 1) incompatibility groups. Two blaVIM-carrying plasmids could not be typed by the database, while another one was integrated into the chromosome. Conclusion We observed the spread of VIM-encoding integrons, mainly of In110, among Enterobacterales isolated from Czech hospitals, but also an increased number of novel elements underlining the ongoing evolution.